Dynamic changes in prognostic nutritional index and systemic immune-inflammation index predict survival following debulking surgery in ovarian cancer - Ohanoglu Cetinel, Karolin; Guner, Gazi; Karabudak, Can Berk; Zeynalli, Emilya; Yavuz Sen, Suheda (Frontiers in Oncology, 2026)
BackgroundOvarian cancer remains the most lethal gynecologic malignancy. Increasing evidence suggests that host immunonutritional status and systemic inflammation—captured by the Prognostic Nutritional Index (PNI) and the Systemic Immune-Inflammation Index (SII)—influence postoperative recovery and survival outcomes.MethodsThis retrospective study included 78 patients who underwent primary debulking surgery for epithelial ovarian cancer. Preoperative and 6-hour postoperative PNI and SII values were calculated, and ΔPNI was defined as the postoperative–preoperative difference. Associations with postoperative inflammatory markers and overall survival (OS) were evaluated using Spearman correlation, Kaplan–Meier analysis, and Cox regression.ResultsPostoperative PNI decreased significantly (49.3 → 34.1; p < 0.001), and SII increased markedly (964.7 → 4003.2; p < 0.001). Lower postoperative PNI and higher preoperative SII were associated with greater postoperative inflammatory response. In multivariate analysis, higher postoperative PNI independently predicted improved OS (HR 0.94, 95% CI 0.89–0.99; p = 0.021), while higher preoperative SII independently predicted worse OS (HR 1.18, 95% CI 1.01–1.36; p = 0.037). ΔPNI and postoperative SII were not independently prognostic.ConclusionPostoperative PNI and preoperative SII provide complementary and independent prognostic information in patients undergoing primary debulking surgery for ovarian cancer. ΔPNI reflects acute immunonutritional stress but does not independently predict survival. Given their accessibility and modifiability, these indices may support perioperative risk stratification and represent potential targets for future interventional studies.